Aquaporin-4 Expression Patterns in Glioblastoma Pre-Chemoradiation and at Time of Suspected Progression. (7th February 2019) - Levy, Michael; Barletta, Scott; Huang, Hwa; Grossman, Stuart A.; Rodriguez, Fausto J.; Ellsworth, Susannah G.; Dzaye, Omar; Holdhoff, Matthias
Abstract: There has been controversy about the presence and potential role of aquaporin-4 (AQP4) in glioblastoma (GBM). We analyzed tissue from 22 patients with newly-diagnosed GBM as well as matching tissue from 17 of these cases who underwent repeat resection for suspected recurrence and performed immunohistochemical analysis for AQP-4 expression. While some degree of AQP4 expression was detected in all 22 cases (39 samples), there was no clear relationship between staining pattern and disease status (active versus inactive GBM) between baseline and time of repeat biopsy. In addition, there was no clear relationship between AQP4 expression and degree of edema.